Viability tests of LIPI-MC mould collection in ampoule of L-drying preservation after one year of storage at 5º C - MUHAMMAD ILYAS (Biodiversitas Journal of Biological Diversity, 2007)
A study on viability test of several LIPI-MC mould isolates in ampoule of L-drying preservation after one year storage at 5º C had been conducted. In this study, cell survival level of 34 ampoules number from eight mould generas and 17 species had been counted. The objective of this study was to observe the survival or viability level of several mould isolates in ampoule L-drying preservation after one year storage at 5º C. The measurement of viability level was based on the average of colony forming unit density (CFU/ml). The result showed that there were seven mould isolates have hingh viabilitiy, 18 isolates have medium viabilitiy, two isolates have low viability, and five isolates have lost its viability.© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: viability, mould, ampoule, L-drying, colony forming unit (CFU/ml).